Lactobacillus plantarum Inoculants Delay Spoilage of High Moisture Alfalfa Silages by Regulating Bacterial Community Composition - Yang, Fengyuan; Wang, Yanping; Zhao, Shanshan; Wang, Yuan (Frontiers in Microbiology, 2020)
The objective of this study was to investigate the mechanism of Lactobacillus plantarum (L. plantarum) involved in improving fermentation quality of naturally ensiled alfalfa under poor conditions. High-moisture wilted alfalfa was ensiled without inoculants (CK) or with inoculation of two L. plantarum additives (LPI and LPII). The pH and fermentation products of silage were determinedafter 30 and 90 d of ensiling. Additionally, the bacterial community compositions were analyzed. The L. plantarum inoculants significantly promoted lactic acid accumulation, and Lactobacillus abundance for both periods. At 90 d, silage in CK exhibited a high pH, a loss in dry matter, and a high concentration of ammoniacal nitrogen. The inoculations of L. plantarum significantly inhibited the growth of Clostridia, and reduced ammoniacal nitrogen concentration in silage (P < 0.05). Thus, inoculation with L. plantarum improved the fermentation quality of alfalfa silage and inhibited the growth of spoilage microorganisms, and further delayed spoilage of alfalfa silage under adverse ensiling conditions.